Comparative study on the power scaling performance of three different coherent polarization beam combination system structures - 马鹏飞 周朴 马阎星 粟荣涛 刘泽金 (Chinese physics B, 2012)
Coherent polarization beam combination （CPBC） is a new kind of coherent beam combination configuration with high combining efficiency and excellent beam quality. In order to extend the CPBC system to a large scale, we provide a comparative study on the power scaling performance of three different coherent polarization beam combination system structures. It is found that the pairwise structure has high tolerance to aberrations and has the potential to extend to a large scale with high combining efficiency. In consideration of all the aberrations, the combining efficiency of the pairwise structure can be attained as high as 90% when the combined beams are more than 200. Some instructive suggestions are given to extend the CPBC system to a large scale.